UNDERSTANDING CORE CAUSE AND ACTION OF DELAY ISSUE FOR AIR EXPORT DOCUMENTS USING LFA - Haryono Haryono; Dhia Rohadatul Ngais; Muhammad Rifni (Institut Transportasi dan Logistik Trisakti, 2017)
Freight forwarding activities includes both export and import. The issue in this study is the lengthy process of document types of general cargo air export, resulting in the delay of release to customers. The research objective is to determine the core and cause of delay in releasing air export document, and the action of it. Research method used in this study is Logical Framework Approach (LFA) to analyze the factors that cause the delay with problem and objective tree by using a technique SMART (specific, measurable, achievable, realistic, and time bound). Results show an increase in number of shipments towards the end of the observed period (12 months) has been accompanied by an increase in the amount of delay in release air export document caused by the constraint in the work process and systems namely, yet integrated of development process of working with systems used, quality of human resources that not all meet the standards should be. The solutions may fit with existing problems is integrating the development process of working with the systems with supported by the quality of human resources for very competitive so as to expedite the process of release air export documents and increase company profit.